IMPACT OF THE TYPE OF DELIVERY ON GROWTH, BODY COMPOSITION AND MOTOR PERFORMANCE OF CHILDREN AND YOUNG PEOPLE - Bessa Dantas, Diego; Fernando dos Santos, João; Muller Reis Weber, Vinicius; Aires Ferreira, Sandra; Roberto Queiroga, Marcos (Arquivos do Mudi, 2023)
The aim of this study was to investigate the impact of cesarean delivery (CD) and normal delivery (ND) on growth, body composition and motor performance of children and young people. The study included 114 children and young people (11 to 18 years old) who were divided into two groups (ND and CD). Participants underwent a battery of anthropometric measurements and motor tests. Children and young people born with CD showed greater performance in the trunk elevation test in extension (flexibility), shorter distance covered (m) in the treadmill test (aerobic resistance), greater amount of subcutaneous tissue and endomorphy component than children and young people born from ND. It was observed that children born with CD in this study had a greater amount of body fat, greater trunk flexibility and shorter distance covered on a treadmill, suggesting important advantages for children born with ND in relation to obesity and aerobic capacity. These components of physical fitness related to health are determinant for the development of chronic degenerative diseases. This study reveals that ND should also be encouraged as a health promotion strategy.